Influence of internet usage on physical activity participation among Chinese residents: evidence from 2017 China General Social Survey - Ji, Min; Deng, Detian; Yang, Xiaojuan (Frontiers in Public Health, 2024)
This study aimed to examine the impact of internet usage on physical activity participation among Chinese residents, utilizing data from the 2017 China General Social Survey (N=12,264). Multiple regression models and a binary Probit model were employed to investigate the relationship between internet usage and physical activity participation, with a focus on exploring the moderating effects of gender, age, and education level. The study found a positive association between increased internet usage and decreased engagement in physical activity (-2.707), supporting the hypothesis that internet usage has a negative influence on physical activity. Results also revealed significant age-related moderating effects, indicating varying patterns of the internet-physical activity relationship across different age groups. Besides, gender and education level were found to significantly moderate this association, suggesting that gender equality and educational attainment have impact on how individuals utilize the internet for physical activity purposes. The study underscores the evolving role of the internet in shaping physical activity behaviors in the Chinese context and emphasizes the importance of considering age-related dynamics in health promotion strategies.